Impact of Different Synchrotron Flattop Operation Modes on 4D Dosimetric Uncertainties for Scanned Carbon-Ion Beam Delivery - He, Pengbo; Li, Qiang (Frontiers in Oncology, 2022)
Purpose: The characteristic of pulsed beam delivery for synchrotron-based carbon-ion radiotherapy has led to the emergence of many scanning scenarios in order to improve the treatment efficiency and accuracy of moving target volume. Here, we aim to evaluate a novel breathing guidance motion mitigation performance under different synchrotron flattop operation modes in carbon-ion radiotherapy. Methods: Using twelve 4DCT datasets of lung cancer patients who had been treated with respiratory-gated carbon-ion pencil beam therapy, range-adapted internal target volume (raITV) plans were optimized. Under the fixed flattop with single-energy and extended flattop with multi-energy synchrotron operation modes, the 4D treatments with breathing guidance and free breathing-based gated phase-controlled rescanning (PCR) beam delivery were simulated. Dose metrics (D95 and D5-D95 in clinical target volume (CTV)) and treatment time of the resulting 4D plans were compared. Results: The two synchrotron operation modes provided different scanning dynamics. For the free breathing-based PCR method delivered in the extended flattop operation mode, the averaged CTV-D95 values were 90.4±3.7 %, 95.4±1.7%, 96.9±1.5%, 97.2±1.5%, and 97.3±1.5% for the 1-scanning, 2-PCR, 4-PCR, 6-PCR, and 8-PCR, respectively. For the breathing guidance-based PCR method delivered in the extended flattop mode, these values were 89.1±4.0%, 97.0±1.4%, 98.2±0.7%, 98.6±0.7%, and 98.9±0.7%, respectively. However, CTV-D95 significantly increased to 98.5±1.0% even with just 1-scanning breathing guidance-based fixed flattop operation mode (p<0.01). Moreover, there was no significant difference in treatment time among the three technical combinations (p>0.15). Conclusions: The combination of the breathing guidance and PCR methods should be an alternative way for motion mitigation for the fixed flattop synchrotron operation mode. The target dose coverage and homogeneity could be further improved by the combination of the breathing guidance and PCR methods than the traditional PCR-only technology for the extended flattop synchrotron operation mode.